2019
DOI: 10.1098/rsbl.2019.0371
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of circadian responses with shorter and shorter millisecond flashes

Abstract: Recent work suggests that the circadian pacemaker responds optimally to millisecond flashes of light, not continuous light exposure as has been historically believed. It is unclear whether these responses are influenced by the physical characteristics of the pulsing. In the present study, Drosophila ( n = 2199) were stimulated with 8, 16 or 120 ms flashes. For each duration, the energy content of the exposure was systematically varied by changing the pulse irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…We note that the variability of individual responses to flashed light is higher than that of continuous light, but commensurate with other studies of flashed lights in humans [19,41] and flies [42], and with the recently identified large individual differences in circadian sensitivities to evening LE [43]. In comparison to continuous light paradigms, flashed light paradigms may be more susceptible to probabilistic photon catch over the short stimulus windows, which may explain the phase advances or near-zero phase shifts seen at low durations (sub-millisecond) in the variable-duration experiment as participants would be more likely to experience a slight non-specific advance that we observe in the control arm of this protocol.…”
Section: Discussionsupporting
confidence: 91%
“…We note that the variability of individual responses to flashed light is higher than that of continuous light, but commensurate with other studies of flashed lights in humans [19,41] and flies [42], and with the recently identified large individual differences in circadian sensitivities to evening LE [43]. In comparison to continuous light paradigms, flashed light paradigms may be more susceptible to probabilistic photon catch over the short stimulus windows, which may explain the phase advances or near-zero phase shifts seen at low durations (sub-millisecond) in the variable-duration experiment as participants would be more likely to experience a slight non-specific advance that we observe in the control arm of this protocol.…”
Section: Discussionsupporting
confidence: 91%
“…Flash durations from 10–1000 µs yield similar phase shifts [ 22 ], as do duration exposures 15–210 min (present study) and flash intensities 30–9500 lux [ 22 ]; the interflash interval has a non-monotonic (rapid peak followed by exponential decay) dose-response relationship [ 10 ]. These data follow observations that outer retinal mechanisms provide a functionally significant ON signal, with a fast decay [ 34 ] to higher-order circadian centers that augment, but are dissociable from, signals originating via melanopsin phototransduction [ 7 ].…”
Section: Discussionsupporting
confidence: 85%
“…44 Introduction of more natural "dynamic" lighting conditions to phase-shifting experiments, though rarely (if ever) practiced in the laboratory, might thus refine PRC waveforms and have special significance for identifying changes to photic PRCs constructed using narrowband and intermittent photic stimuli. 45,46 Another future consideration involves the use of graded twilight simulations. Though virtually all phase-shifting studies to date have been conducted in the laboratory under square-wave LD cycles carrying abrupt (switch-like) transitions between lights-on and lights-off, inclusion of natural twilight progressions-over the course of 60-90 minutes-might signal (or aid in the communication of) other seasonal factors to the pacemaker that impact the shape of the PRC manifesting under different photoperiods.…”
Section: Discussionmentioning
confidence: 99%